SECURITY SISTEM PADA BRANKAS DENGAN KARTU E-KTP DAN PASSWORD BERBASIS GERBANG LOGIKA MENGGUNAKAN KOMBINASI IC TTL - Muarif, Muarif; Mardiansyah, Mardiansyah; Romdhoni, Romdhoni (Infotronik : Jurnal Teknologi Informasi dan Elektronika, 2024)
A safe is designed to securely store valuable items, including important documents, jewelry, money, and other precious belongings. Modern safes often feature manual or semi-automatic locking systems, such as combination locks or cylinder locks. However, combination locks can be less secure and efficient, making them vulnerable to theft. In Indonesia, the adoption of RFID (Radio Frequency Identification) technology, especially in E-KTP cards, has seen progress, though its potential remains underutilized. This research integrates an advanced logic gate circuit using IC gates—AND, XOR, and NOT—functioning as a password mechanism. The device operates by requiring users to tap their E-KTP against a reader to unlock the safe door. Upon a successful tap, an LCD screen displays relevant information and requests a 16-bit binary password made up of 8 "1s" and 8 "0s." Users have 20 seconds to input the correct password; exceeding this time will reset the system, prompting another E-KTP tap. If an unregistered E-KTP is used, access is denied. The RFID reader, functioning at a frequency of 13.56 MHz, can read the E-KTP ID from a maximum distance of 1.3 cm. The integrated circuit logic will output HIGH only when the entered binary password matches the pre-set code within the safe, ensuring a secure and efficient locking mechanism for valuable items.